Management of uplandd watersheds: participation of the mountain communities - Bochet, Jean-Jacques (Rome, 1986)
The purpose of this paper is to examine the role of mountain communities in the design and implementation of watershed management programmes, in short, their moral commitment to and physical and material participation in these programmes. Part one analyses the problem and its effect on various socio-economic groups. Part two looks at the administrative structures and legal regulations for intervention, socio economic data gathering and analysis, planning and programming. Part three deals with implementation: the role of the community and methods to be used.
Keywords: Watersheds